CO2 abatement from the iron and steel industry using a combined Ca–Fe chemical loop. (15th May 2016) - Tian, Sicong; Li, Kaimin; Jiang, Jianguo; Chen, Xuejing; Yan, Feng
Graphical abstract: Highlights: FeO/Fe2 O3 redox and CaO/CaCO3 calcination cycles are coupled for an auto-thermal CO2 capture. The highly exothermic oxidation of FeO drives the energy-intensive CaCO3 calcination reaction. The material developed exhibits a stable cyclic CO2 uptake and appreciably reduced net heat demand. The combined Ca–Fe chemical loop proposed is promising for CO2 capture from iron and steel industry. Abstract: We report an integrated CO2 capture process to manufacture iron and steel with low CO2 emissions from steel-making plants over a CaO-based, Fe-functionalized CO2 sorbent. This new process relies on a combined Ca–Fe chemical loop, where the exothermic oxidation of FeO provides the heat (or fractions of it) required to drive the endothermic decomposition of CaCO3 . A key advantage of coupling a FeO/Fe2 O3 redox cycle and a CaO/CaCO3 CO2 capture cycle within the as-prepared materials is that the heat could be transferred from FeO to CaCO3 directly at a molecular level. All materials synthesized require an appreciably reduced net heat, i.e. a decrease of 26–43%, for CaCO3 decomposition during the combined Ca–Fe looping when compared with conventional calcium looping. Importantly, materials CaFe-CA1 EG1 -pH1, CaFe-CA1 EG1 -pH2, and CaFe-CA1 EG1 -pH3 exhibit a fairly stable cyclic CO2 uptake of ∼0.16 gCO2  gsorbent −1 throughout 10 realistic combined Ca–Fe looping cycles. The medium capacity but excellent stability for CO2 capture of the CO2 sorbents makes them a promising alternative of naturally-derived, CaO-based materials, especially for the combined Ca–Fe chemical loop proposed. Using steel slag as feedstock, the material developed is very promising for CO2 abatement from the iron and steel industry accompanied by the recycling of CaO and Fe2 O3 components in spent sorbents and recovery of energy from process gases.